Adapting pervasive systems to multiuser privacy requirements. (16th July 2008) - Ortmann, Steffen; Langendorfer, Peter; Maaser, Michael
In this paper, we discuss how diverging privacy requirements in a multiuser ubiquitous environment can be satisfied. We are investigating how to ensure that the requirements of concerned as well as open-minded users can be satisfied, simultaneously. In order to reduce overhead and increase granularity of the objects to be managed, we propose to cluster all available sensors, creating objects we denote as virtual sensors. All further operations are done on the virtual sensors. We will discuss our management architecture and present our simulation environment showing how the pervasive environment automatically adapts to user requirements and user locations.